Quality of life, stress, anxiety and depression and associated factors among people with type 2 diabetes mellitus in Western region Saudi Arabia - Abualhamael, Shahad Abduljalil; Baig, Mukhtiar; Alghamdi, Waleed; Gazzaz, Zohair Jamil; Al-Hayani, Majid; Bazi, Abdulrahman (Frontiers in Psychiatry, 2024)
The objective of this study is to evaluate the quality of life (QoL), depression, anxiety, and stress (DAS), along with associated factors among individuals with diabetes in Saudi Arabia.Methods: This survey was conducted at King Abdulaziz University (KAU), Jeddah, Kingdom of Saudi Arabia (KSA). The assessment of depression, anxiety, and stressDAS related to Type 2 Diabetes Mellitus (T2DM) was conducted using the DASS-21 questionnaire, while diabetes-related QoL was evaluated using the revised version of the diabetes QoL questionnaire (RV-DQoL13). Data were analyzed using SPSS-26.Results: A total of 251 subjects were included in the study (165 [65.7%] males and 86 [34.3%] females, mean age 50.1 ± 14.5 years). The individuals with DM had a mean value of QoL of 29.16 ± 9.23, with 46.9% having poor QoL. Furthermore, in dimensions of QoL, almost half of the individuals reported high worry about the disease (49.6%), followed by a high diabetes impact (46.6%) and low life satisfaction (42.9%). The prevalence of depression, anxiety, and stressDAS was 49.4%, 71.7%, and 49.8%, respectively. A significant correlation was found between depression, anxiety, and stressDAS and DASS-21 scores with QoL (p<0.001). The regression analysis indicated an association of distinct factors with QoL like age above 41 years (p=0.004), being married (p<0.001), being divorced (p=0.04), higher education (p=0.007), regular medicine intake (p=0.01), regular exercise (p=0.03), lipid profile (p=0.01), HbA1c (p<0.001), and DASS-21 scores (p<0.001). Poor QoL score (TQoL score > 27) was significantly associated with depression, anxiety, and stressDAS (p<0.001). The participants with higher monthly income, shorter disease duration, regular medicine use, and altered lipid profiles, and older subjects had a lower chance of depression, anxiety, and stress.Approximately half of individuals with T2DM experienced poor QoL, while the prevalence rates for depressionstress, anxiety, and stress depression were 49.4%, 71.7%, and 49.8%, respectively. Scores in the domains of impact, worry, and satisfaction were below optimal levels. Several factors were linked to QoL and depression, anxiety, and stressDAS, and an association was observed between DASS-21 scores and QoL.